The Joke as a Medium - Braga, Adriana A.; Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2025)
We argue that jokes are not just about the ha-ha and laughter, but they are a technology,and a medium that create an environment and they have a serious purpose. We examine the mediumof the joke making particular use of the work of three scholars who made a serious effort to understandthe phenomenon of the joke and humor, namely Sigmund Freud (1916) in his book Jokes and TheirRelation to the Unconscious, Johan Huizinga (1971) in his book Homo Ludens and Marshall McLuhan(1964) in his book Understanding Media and his other writings. For Freud jokes like dreams are themedium to reach the unconscious mind. For Huizinga play, puns and games that are closely related tojokes are a universal aspect of human culture dating back to our very origin. For McLuhan jokes areabout grievances and a way people deal with them.